Formulation And In Vitro Evaluation Of Tamoxifen Ethosomal Gels For Transdermal Delivery - Assi, Reem Abou (2024)
Breast cancer (BC) poses a significant global health concern, accounting for 2.3 million cases and 685,000 deaths in 2020. Among these cases, two-thirds involve hormone receptor-positive tumours, characterised by estrogen receptors that fuel cancer growth. Tamoxifen stands as the conventional therapy and preventive measure for women at risk or already afflicted by hormone receptor-positive BC. However, oral tamoxifen encounters obstacles such as limited absorption due to hydrophobicity and liver first-pass effect, along with severe side effects including fatty liver disease, blood clots, and a heightened risk of endometrial cancer. To mitigate these adverse effects, this work investigated the localised tamoxifen transdermal delivery utilising the ethosomal system as an alternative administration route to oral intake. The current research work has involved studying three distinct classes of ethosomes: transethosomes employing Tween 20®, Span 20®, and Span 80®, bilosomes using sodium taurocholate and sodium cholate, and invasomes incorporating limonene and isophytol. The study encompassed seven separate 24 factorial designs to assess the impact of lipid, ethanol, penetration enhancer concentrations, and extrusion times on key parameters like particle size (PS), dispersity (Đ), and zeta potential (ZP). Only formulations meeting specific criteria proceeded to entrapment efficacy studies. Among the investigated incorporated concentrations of tamoxifen (0.6, 1, and 1.4 mg/ml), 1 mg/g was selected.